STEM education through PhET simulations: An effort to enhance students’ critical thinking skills - Khaeruddin, Khaeruddin; Bancong, Hartono (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2022)
One of the primary purposes of physics education is to help students develop critical thinking abilities to solve everyday situations. The purpose of this research is to investigate the impact of STEM education using PhET simulation on students' critical thinking skills. A pre-experimental approach with a one-group pre-test post-test design was used in this study. There were no control or comparator groups in this study, which was done in a single group. This study was carried out in a high school in Makassar during the even semester of the 2020/2021 academic year. The research population consisted of 110 students separated into three classes. Using a simple random sampling technique, a sample of 37 students from class XI IPA2 was chosen. The results revealed a significant increase in students' critical thinking skill scores after the implementation of STEM Education using PhET simulation. The students’ pre-test means score in linear motion material is 68.18, and it increased (N gain = 0.45) after STEM education through PhET simulation is applied. Likewise, the students' pre-test means score in Newton's Law material was 66.33 and rose significantly to 81.96 (N gain = 0.46) in the post-test. Therefore, this study concludes that STEM education through PhET simulations can improve students' critical thinking skills in both linear motion and Newton's laws materials. This study has implications, especially for physics teachers in improving students' critical thinking skills by using STEM education through PhET simulations.